Fracture of Intravenous Cannula in External Jugular Vein: A Case Report - Mishra, Shivangi; Arayamparambil Vijayan, Padmakumar; Suresh Chandan, Garud; Prathapan Sarada, Pooja (International Research in Medical and Health Sciences, 2020)
Peripheral venous cannula insertion is one of the most common invasive procedures performed. The external jugular vein is a commonly used site for peripheral intravenous cannulation for the administration of fluids, medications, low dose vasopressors, and electrolyte correction. Various complications have been reported with it, cannula fracture being one of the rarest. We report a case of fracture of a peripheral intravenous cannula in the external jugular vein. While removal of two days old peripheral intravenous cannula from the external jugular vein, the cannula was noticed to be fractured at the entry site. The fractured fragment of the cannula was safely removed by surgical incision and phlebotomy. Early recognition, confirmation of position, and removal are a mainstay of management. Steps for prevention of such occurrences including proper care, a good technique of insertion, and training of staff should be adopted.